PENGARUH PENERAPAN PENDEKATAN KONTEKSTUAL TERHADAP KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA SMP - Suwanjal, Usep (AKSIOMA (Jurnal Pendidikan Matematika), 2016)
Critical thinking skills of mathematics mastered by students is very important, especially in the competition of globalitation era. An approach that can improve both of them is contextual approach in learning. This research aims are to determine: The Improvement of students critical thinking skills between the class which used contextual approach in learning and the one which used conventional learning. Quasi-experiment methods was used in the research Â and the design was "pretest-posttest non equivalent control group". Population of this research was the students of SMP Negeri 3 Menggala and class VIII C and VIII D as the research sample, technique of samples used purposive sampling. Data collected by the instrument test critical thinking of mathematics. The improvement of critical thinking skills data analysed by using the t- test. The findings of this study indicated: Â The Improvement of students critical thinking skills between the class which used contextual approach in learning was better than which used conventional learning. In table t-test indicated sig < Î± is 0.001 < 0.05Keywords : contextual approach, critical thinking skills of mathematics